Docetaxel causes lymphatic endothelial cell apoptosis and impairs lymphatic function and gene expression in vitro. Issue 2 (2021) - Wong, AM; Baik, JE; Park, H; Li, C; Shin, JY; Kataru, RP; Mehrara, BJ
No abstract available